Exploiting the Freshwater Shrimp Neocaridina denticulata as Aquatic Invertebrate Model to Evaluate Nontargeted Pesticide Induced Toxicity by Investigating Physiologic and Biochemical Parameters - Petrus Siregar; Michael Edbert Suryanto; Kelvin H.-C. Chen; Jong-Chin Huang; Hong-Ming Chen; Kevin Adi Kurnia; Fiorency Santoso; Akhlaq Hussain; Bui Thi Ngoc Hieu; Ferry Saputra; Gilbert Audira; Marri Jmelou M. Roldan; et al. (MDPI AG, 2021)
As a nicotinoid neurotoxic insecticide, imidacloprid (IMI) works by disrupting nerve transmission via nicotinic acetylcholine receptor (nAChR). Although IMI is specifically targeting insects, nontarget animals such as the freshwater shrimp, Neocaridina denticulata, could also be affected, thus causing adverse effects on the aquatic environment. To investigate IMI toxicity on nontarget organisms like N. denticulata, their physiology (locomotor activity, heartbeat, and gill ventilation) and biochemical factors (oxidative stress, energy metabolism) after IMI exposure were examined. IMI exposure at various concentrations (0.03125, 0.0625, 0.125, 0.25, 0.5, and 1 ppm) to shrimp after 24, 48, 72 h led to dramatic reduction of locomotor activity even at low concentrations. Meanwhile, IMI exposure after 92 h caused reduced heartbeat and gill ventilation at high concentrations. Biochemical assays were performed to investigate oxidative stress and energy metabolism. Interestingly, locomotion immobilization and cardiac activity were rescued after acetylcholine administration. Through molecular docking, IMI demonstrated high binding affinity to nAChR. Thus, locomotor activity and heartbeat in shrimp after IMI exposure may be caused by nAChR blockade and not alterations caused by oxidative stress and energy metabolism. To summarize, N. denticulata serves as an excellent and sensitive aquatic invertebrate model to conduct pesticide toxicity assays that encompass physiologic and biochemical examinations.